Data on the vegetation and biogeography of the Picos de Europa - Rivas Martínez, Salvador; Pizarro, José (Acta Botanica Malacitana, 1988)
It is released some types of higrophile and peat bogs vegetation in the altimontano bioclimatic stage from Picos de Europa mountains (Cantabria, Espan?a); likewise it is specified the limits and phytocenotic criteria that permit to recognize the Picoeuropeano and Altocarrionds subsectors in such mountainous territory.